Duitsland - 35 jaar later : Berufsverbot : feiten en achtergronden. - Altvater, Elmar; Neusüss, Christel; Abendroth, Wolfgang (Amsterdam : SUA, 1977)
Bibliotheek François Vercammen
Nederlands
Monografie